Opioid-free anesthesia with esketamine combined with interpectoral plane block and pectoralis-serratus plane blocks in radical mastectomy: a randomized controlled trial - Ding, Wenping; Deng, Youming; Sun, Nuo; Wang, Rongguo; Liu, Qian; Zhang, Yan; Zhou, Meiyan; Liu, Yan; Wang, Liwei (Frontiers in Pharmacology, 2025)
ObjectiveOpioid-free anesthesia (OFA) is an emerging technique that aims to reduce or eliminate intraoperative opioid use. Previous studies have shown that OFA is associated with reduced postoperative opioid consumption and fewer adverse events. This study investigated the impact of OFA on the quality of recovery (QoR) in patients undergoing radical mastectomy for breast cancer.MethodsWe enrolled 130 patients scheduled for radical mastectomy and randomly assigned them to either the opioid-free anesthesia (OFA) group or the opioid-based anesthesia (OA) group. Data from 124 patients were ultimately analyzed. The primary outcome was the Quality of Recovery-40 (QoR-40) score at 24 and 48 h postoperatively. Secondary outcomes included the Numerical Rating Scale (NRS) pain scores at 30 min, 24 h, and 48 h postoperatively, perioperative hemodynamic parameters, post-anesthesia care unit (PACU) stay duration, and the incidence of related adverse events.ResultsPostoperative QoR-40 scores were significantly higher in the OFA group than in the OA group at both 24 h (176.1 ± 3.7 vs 169.7 ± 3.3; mean difference 6.4, 95% CI 5.2–7.7, p < 0.001) and 48 h (180.3 ± 2.7 vs 173.7 ± 3.6; mean difference 6.6, 95% CI 5.5–7.7, p < 0.01). The OFA group showed significantly lower pain scores on the Numeric Rating Scale (NRS) at all measured time points (30 min: 1.89 ± 0.8 vs 2.36 ± 1.2; 24 h: 1.21 ± 0.6 vs 1.66 ± 0.8; 48 h: 1.03 ± 0.4 vs 1.28 ± 0.6, all p < 0.05). No statistically significant differences were observed in hemodynamic parameters, including mean arterial pressure (MAP) and heart rate (HR), at the following time points: upon entering the operating room (T0), before anesthesia induction (T1), before tracheal intubation (T2), immediately after tracheal intubation (T3), at skin incision (T4), 10 min after incision (T5), and upon leaving the operating room (T6). However, the incidence of postoperative nausea and vomiting (PONV) differed significantly between the two groups at 30 min, 24 h, and 48 h postoperatively (p < 0.05).ConclusionFor patients undergoing radical mastectomy, opioid-free anesthesia (OFA) utilizing esketamine combined with Interpectoral Plane (IPP) and Pectoralis-Serratus Plane (PSP) blocks significantly improved postoperative recovery quality compared to conventional opioid-based anesthesia (OA).